Application of hydrothermal time model to determine the cardinal temperatures for seed germination in crops (A case study; velvetleaf (Abutilon theophrasti med.)) - Esmaeil Yasari; Mousa Miri; Sadegh Atashi; mohsen jamali (علوم و فناوری بذر ایران)
This study was evaluated the ability of a hydrothermal time model (HTT) to describe the kinetics of seed germination in crops and also to determine the cardinal temperatures for germination (as a case study; velvetleaf). For this purpose, the experiment was carried out at eight constant temperature regimes (T; 15, 20, 25, 30, 35, 37, 40 and 42°C) at each of the following water potential (ψs; 0, –0.18, –0.36, –0.54 and –0.72 MPa; using PEG 6000). The results indicated that ψ influenced germination rate and germination percentage (P < 0.0001). For this seed lot, cardinal temperatures were 11.8°C for Tb, 35.4°C for To and 45.2°C for Tc in the control (0 MPa) treatment. There was a decrease in hydrotime constant (θH) when T was increased to To and then remained constant at supra-optimal Ts (24 MPa h-1). At the Ts above To, ψb(50) values increased linearly with T. The kT value (the slope of the relationship between ψb(50) and T exceeds To) of this seed lot was calculated as 0.1011 MPa°Ch-1. Moreover, the ψb(50) was estimated to be –0.91 MPa based on this model. Our results show that when the HTT model is applied, it can accurately describe germination response of velvetleaf around Ts and ψs.